Understanding the Nigerian stock market - Odife, Dennis O. (New york : Vantage Press, 1984)
This book provides a basic introduction to the Nigerian Stock market as such is of interest to students of the stock market.
Includes Q&A
ijb13/08/2018
Loans
Keywords: Capital market; Nigeria